Love that dog - Creech, Sharon (New York : HarperCollins, 2001)
A young student, who comes to love poetry through a personal understanding of what different famous poems mean to him, surprises himself by writing his own inspired poem.
Keywords: Poetry -- Fiction; Novels in verse